Development of Non- Invasive Cholesterol Monitoring System Using TCRT5000 Sensor with Android Compatibilty - Rahmawati, Tika; Tasyakuranti, Alvania Nabila; Sumarti, Heni; Kusuma, Hamdan Hadi (Jurnal Fisika, 2023)
High cholesterol levels cause several diseases, such as atherosclerosis (narrowing of the arteries), coronary heart disease, high blood pressure, obesity, thyroid disorders, diabetes mellitus, liver disease, and kidney disease. Generally, such checking is carried out invasively in clinical laboratories or hospitals. The checking can be done individually at a lower cost by using non invasive cholesterol measuring devices. This study aims to design and implement an android-based non-invasive cholesterol monitoring device using the TCRT5000 sensor. The tool developed was tested to measure cholesterol levels in 15 respondents aged 20-30 years. The research procedure consisted of several stages, starting with the design stage of the tool, which was carried out by assembling the components; the second stage was the tool coefficient of determination test, the third stage was the accuracy test, and the last stage was the data transfer speed test. The average accuracy of the tool is 83.18%, and the avarage of delay is 8.8 ms. This tool has considerable potential to be used in a telemedicine system that can be accessed remotely regularly to determine the estimated value of cholesterol levels in the blood.